(untitled) (Journal of Environmental Microbiology and Toxicology, 2014)
For the past 30 years more than 600 different disinfection by-products (DBPs) have been reported with many unknown ones yet to be discovered. Bioluminescence rapid toxicity tests are suitable toxicity screening for DBPs that caused adverse health effects. Previously, IC50 study on specific DBPs have not been conducted. This study aims to characteristically identify the sensitivity of bioluminescent rapid bioassays on selected DBPs (chloroacetic acid, trichloroacetic acid, bromoacetic acid and iodoacetic acid) by measuring IC50 of Vibrio fischeri on these compounds. IC50 are determined through luminescence that was measured using a Beckman Counter DTX 800 multimode detector. The 30-minute IC50 of selected DBPs are as followed: CAA (865.4 mg/L), TCAA (1119 mg/L), BAA (59.67 mg/L) and IAA (15.6 mg/L). It was found that Bioluminescent Rapid Bioassays based on Vibrio fischeri showed promising sensitivity on the selected DBPs and are suitable as a screening tools for DBPs.